(untitled) (Terr@ Plural, 2020)
The graphic representations have privileged space in the journeys made by naturalists since the Eighteenth century and they are fundamental elements of the geographical analysis. The main goal of this paper is to reflect on the illustrations that composed geographies of Brazil brought by the Philosophical Journey of the naturalist Alexandre Rodrigues Ferreira in the Eighteenth Century. First, it is presented the relevancy of the expeditions taken by naturalists as well as the importance of the images produced by such expeditions in the consolidation of Geography as a discipline. Next, it is discussed the journey made by Alexandre Rodrigues Ferreira in his Philosophical Expedition throughout Brazil. Lastly, it is analyzed the creation of images and imaginaries about Brazil at the time the graphic representations were produced.